Noncanonical wnt signaling in the integrity of the blood-testis barrier and sperm release - Rey, Rodolfo Alberto (2021)
The mammalian testis is formed by 2 morphologically and functionally distinct compartments: the seminiferous tubules and the interstitial tissue. The seminiferous tubules contain the germ cell population, originating the male gametes in the adult, and the somatic Sertoli cell lineage. In the interstitial tissue lies the Leydig cell population, responsible for androgen secretion, amid connective tissue with blood vessels and nerves. The structure and function of the testes show remarkable changes during postnatal life, especially during pubertal maturation, driven by androgens. One notorious transformation occurs within the seminiferous tubules: prepubertal spermatogenesis, limited to spermatogonial mitoses, switches to adult spermatogenesis, where spermatogonial proliferation is followed by 2 successive meiotic divisions and spermatid maturation leading to the production and release of spermatozoa. This gonad-specific biologic process depends essentially on the support given by mature Sertoli cells. While molecules coming from the blood vessels present in the interstitial tissue have free access to spermatogonia, meiotic and postmeiotic germ cells are completely isolated from blood-borne substances. This is mainly due to the development of the blood-testis barrier (BTB) during pubertal maturation.